La ‘copia’ architettonica. Un’introduzione storico-teorica - Ricci, Maurizio (Aesthetica Preprint, 2024)
The concept of ‘copy’, which had such an importance in the history of the figurative arts and artistic academies, encounters many difficulties, especially of a theoretical nature, when one tries to apply it to architectural works. The greatest difficulty consists in the fact that a true and proper copy, in all respects, of an architectural work, therefore not in the ‘symbolic’ sense that the Middle Ages attributed to this term, almost always arises for reasons related to the desire to reconstruct, where it was and as it was, a building lost or seriously damaged due to natural events, war, or the neglect and vandalism of men. On the other hand, the case is different for those architectural works in which there is the ‘artistic will’ to compete with a historical exemplum which, although not imitated in all its components, therefore without the will to make a copy, nonetheless rises to a model of reference, as in the Renaissance, to which the most recent work alludes in a subtle game of cross-references, rather than being a simple replica.